2020
DOI: 10.24843/ejmunud.2020.v09.i04.p11
|View full text |Cite
|
Sign up to set email alerts
|

Peran Komitmen Organisasional Dalam Memediasi Pengaruh Kepemimpinan Transformasional Terhadap Turnover Intention Karyawan Ambiente Spa

Abstract: Turnover intention is form of movement of employees which can lead to employee leaving. The purpose of study was to examine the effect of transformational leadership on turnover intention mediated by organizational commitment. The study was conducted at Ambiente Spa with 100 samples, using the saturated sample method and data collected through interviews and questionnaires. Classic Assumption Test and Path Analysis were used. Transformational leadership has positive and significant influence on organizational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The results of this study are in line with the research conducted Wanggi et al(2019) and (Paramita & Hendratmoko, 2021) On different objects that prove that transformational leadership styles are not in line with efforts to mitigate turnover rates directly when there are inconsistencies in leadership roles. This study had different results with (Alkarabsheh et al, 2022;Dewi & Dewi, 2020;Waskita, 2022) which found a negative effect of transformational leadership on turnover intention…”
Section: Transformational Leadership Towards Turnover Intentionmentioning
confidence: 64%
“…The results of this study are in line with the research conducted Wanggi et al(2019) and (Paramita & Hendratmoko, 2021) On different objects that prove that transformational leadership styles are not in line with efforts to mitigate turnover rates directly when there are inconsistencies in leadership roles. This study had different results with (Alkarabsheh et al, 2022;Dewi & Dewi, 2020;Waskita, 2022) which found a negative effect of transformational leadership on turnover intention…”
Section: Transformational Leadership Towards Turnover Intentionmentioning
confidence: 64%